Class-Size Caps, Sorting, and the Regression-Discontinuity Design - Urquiola, Miguel; Verhoogen, Eric (American Economic Review, 2009)
This paper examines how schools' choices of class size and households' choices of schools affect regression-discontinuity-based estimates of the effect of class size on student outcomes. We build a model in which schools are subject to a class-size cap and an integer constraint on the number of classrooms, and higher-income households sort into higher-quality schools. The key prediction, borne out in data from Chile's liberalized education market, is that schools at the class-size cap adjust prices (or enrollments) to avoid adding an additional classroom, which generates discontinuities in the relationship between enrollment and household characteristics, violating the assumptions underlying regression-discontinuity research designs. (JEL D12, I21, I28, O15)